Propagación de la marea en la zona de Islas Malvinas y Namuncurá/Banco Burdwood - Banegas, Luciano (2020)
Artículo de Banegas, L.; Oreiro, F. A.; Canero, M. F.; Fiore, M. M. E.; perteneciente a la revista Defensa Nacional Nº 4.